Impact of Family and Cultural Upbringing on Young Women’s Perception of Motherhood: A Comparative Study among Sri Lankan and Indian Female College Students - Kosala, L.; Jayathunga, J.T.U.; Lakshman, Iresha; Ashraf, Yasir (European Scientific Journal, ESJ, 2025)
Fertility rates in South Asia have declined significantly over the past four decades, with Sri Lanka and India leading this demographic transition. This study examines the impact of the socialization process experienced by young, unmarried female undergraduates in both Sri Lanka and India on their perceptions of motherhood and the declining fertility rate in contemporary times. Utilizing a mixed-method and pseudo-longitudinal design, the research compares students from the University of Colombo in Sri Lanka and the VET Institute of Arts and Science in Tamil Nadu, India. The results indicate that while traditional ideals around motherhood remain deeply rooted, young women in both countries are actively renegotiating these roles through educational pursuits, career aspirations, and broader exposure to global norms in varying degrees. Cultural expectations and family pressures all contribute to shaping their evolving perspectives. While Indian students exhibit greater confidence in balancing motherhood and career, Sri Lankan students encounter stronger patriarchal norms and more limited institutional support. Statistical data from over 500 participants reinforce these findings, with distinct patterns emerging across academic disciplines, years of study, and socio-economic backgrounds. This study contributes to understanding the demographic shifts in Sri Lanka and India while providing policy-relevant insights into gender, education, and reproductive decision-making.